CAD-based off-line robot programming - Neto, Pedro; Pires, J Norberto; Moreira, A Paulo (2010 IEEE Conference on Robotics, Automation and Mechatronics, 2010)
Traditional industrial robot programming, using the robot teach pendant, is a tedious and time-consuming task that requires technical expertise. Hence, new and more intuitive ways for people to interact with robots are required to make robot programming easier. The goal is to develop methodologies that help users to program a robot in an intuitive way, with a high-level of abstraction from the robot language. In this paper we present a CAD-based system to program a robot from a 3D CAD environment, allowing users with basic CAD skills to generate robot programs off-line, without stop robot production. This system works as a human-robot interface (HRI) where, through a relatively low cost and commercially available CAD package, the user is able to generate robot programs. The methods used to extract information from the CAD and techniques to treat/convert it into robot commands are presented. The effectiveness of the proposed method is proved through various experiments. The results showed that the system is easy to use and within minutes an untrained user can set up the system and generate a robot program for a specific task. Finally, the time spent in the robot programming task is compared with the time taken to perform the same task but using the robot teach pendant as interface.